1986
DOI: 10.1523/jneurosci.06-12-03505.1986
|View full text |Cite
|
Sign up to set email alerts
|

Microcircuitry of the dark-adapted cat retina: functional architecture of the rod-cone network

Abstract: The structure of the rod-cone network in the area centralis of cat retina was studied by reconstruction from serial electron micrographs. About 48 rods converge on each cone via gap junctions between the rod spherules and the basal processes of the cone pedicle. One rod diverges to 2.4 cones through these gap junctions, and each cone connects to 8 other cones, also through gap junctions. A static cable model of this network showed that at mesopic intensities, when all rods converging on a cone pedicle are cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
186
2
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(208 citation statements)
references
References 43 publications
19
186
2
1
Order By: Relevance
“…This apparent discrepancy with one of the results from tests of APB-treated monkeys (38) The symptom of night blindness cannot be entirely explained by the defect in signal transmission between rods and their ON bipolar cells, because rods have alternative electrical connections to the inner retina that bypass the ON bipolar cells (46). In the area centralis of the cat retina, anatomic studies have shown that each cone has electrical gap junctions with Ϸ48 neighboring rods (47). Rod signals can be transmitted to cones through these gap junctions and thence to cone bipolar cells and ganglion cells (48)(49)(50).…”
Section: Discussionmentioning
confidence: 98%
“…This apparent discrepancy with one of the results from tests of APB-treated monkeys (38) The symptom of night blindness cannot be entirely explained by the defect in signal transmission between rods and their ON bipolar cells, because rods have alternative electrical connections to the inner retina that bypass the ON bipolar cells (46). In the area centralis of the cat retina, anatomic studies have shown that each cone has electrical gap junctions with Ϸ48 neighboring rods (47). Rod signals can be transmitted to cones through these gap junctions and thence to cone bipolar cells and ganglion cells (48)(49)(50).…”
Section: Discussionmentioning
confidence: 98%
“…Interaction between the rod and cone pathways is extensive: rods and cones are electrically coupled (Raviola and Gilula, 1973;Smith et al, 1986;Schneeweis and Schnapf, 1995;Krizaj et al, 1998;Tsukamoto et al, 2001), and rod signals piggyback onto cone pathways at several stages in visual processing (for review, see Völgyi et al, 2004). This interaction of the two photoreceptor systems is essential for adaptation of photoreceptor sensitivity to different levels of ambient illumination.…”
Section: On the Distinctive Roles Of Horizontal Cell Somata And Axon mentioning
confidence: 99%
“…Conecone coupling increases with light adaptation in the turtle (Copenhagen & Green, 1987), as does rod-cone coupling in salamander (Yang & Wu, 1989). These changes influence the functional efficacy of the output synapse (Smith et al, 1986) as well as rod input into the cone system.…”
Section: Introductionmentioning
confidence: 99%